Solve for x. -3x = -15
A. X=-5
Original conversation
User: Solve for x. -3x = -15

Weegy: A. X=-5
nicolevaughan16|Points 156|

User: Solve for x. 5x - 1 = 26

Weegy: 5x - 1 = 26; 5x = 27; x = 27/5. The answer is A. x = 27/5
debnjerry|Points 13661|

User: In the solution of the equation 5 - 3x = 2x + 9, 3x is added to the equation first. Which of the following should be done next?

Weegy: (3x-2) squared is 9x^2 - 12x + 4.
twistedechoes|Points 26|

User: What is the solution set of the following equation? -8x + x + 15 = -7x + 12

Weegy: INPUT THE NUMBERS like for f(2) you would put 2(2)^2-7(2)+3= the answer. thank you for using weegy
spartan967|Points 20|

User: Solve for x. 5(2x - 1) = 6

Weegy: B.x = 11/10
jher000|Points 2543|

User: Solve for x. 3(3x - 1) + 2(3 - x) = 0

Weegy: 3(3x - 1) + 2(3 - x) = 0 ; 9x - 3 + 6 - 2x = 0 ; 7x +3 = 0 ; 7x = -3 ; x = -3/7. The answer is B. x = -3/7
debnjerry|Points 13661|

User: Solve for B. R = x(A + B)

Weegy: 1/a+b+x=1/a+1/b+1/x =>(1/a+b+x)-1/x=1/a+1/b Taking (a+b+x)x as LCM, =>x-(a+b+x)/(a+b+x)x=b+a/ab =>-(a+b)/x2+ax+bx=a+b Cancelling (a+b) from both sides we get, => -1/x2+ax+bx=1/ab => x2+ax+bx= -ab =>x2+ax+bx+ab=0 => x(x+a)+b(x+a)=0 =>x+b=0 [ or x+a=0 =>x=-b or x=-a ]
shobhna|Points 80|

User: The first side of a triangle measures 5 in. less than the second side, the third side is 3 in. more than the first side, and the perimeter is 17 in. How long is the third side? If s represents the length of the second side, which of the following represents the length of the third side?

Weegy: s-2 is the length of the third side. s=8 so the length of the third side is 6.

Question
Updated 6/1/2011 8:07:43 AM
Rating
3
-3x = -15; x = -15/-3; x = 5

Questions asked by the same visitor
TrueFalse As a change of state is occurring, the temperature of the system does not change.
Weegy: True. During the change of state, the molecules of a substance absorb energy to overcome the strong intermolecular force of attraction between them. Hence the heat enegy which we supply is absorbed by them for this purpose. [ So change in temperature is not observed. ] (More)
Question
Popular Conversations
Evaluate. -|-7 3| User: A man invests a certain amount of money at ...
Weegy: Let the man invest an amount x at 2% interest. Then, [ he invests an amount (x+800) at 4% interest. Total ...
(-d + 4)(-d - 4) User: Simplify b(a + b) - a(a - b). User: (y 3 - ...
Weegy: (y^3 - 125) (y - 5) = y^4 - 5y^3 - 125y + 625; User: Simplify 5 + 2{x - 4[3x + 7(2 - x)]}. User: 48a 3 bc 2 ...
Soviet armies fighting Germany benefited from a. Polish aid. b. cold ...
Weegy: Soviet armies fighting Germany benefited from COLD WEATHER. User: Erwin Rommel Weegy: Erwin Rommel was a ...
All of the following are correct EXCEPT: a. China now encourages ...
Weegy: All of the following are correct EXCEPT: a. China now encourages families to have many children. ] User: ...
Which of the following terms could be applied to the United States ...
Weegy: Free press could be applied to the U.S. during the Cold War. User: Which of the following technologies was ...
Cardiovascular exercise causes your lungs to breathe less ...
Weegy: Cardiovascular exercise causes your lungs to breathe less often. FALSE. Breathing rate increases during ...
Weegy Stuff
S
P
L
Points 957 [Total 1618] Ratings 2 Comments 937 Invitations 0 Offline
S
Points 350 [Total 711] Ratings 2 Comments 330 Invitations 0 Offline
S
L
P
P
P
Points 156 [Total 3699] Ratings 0 Comments 156 Invitations 0 Offline
S
Points 137 [Total 418] Ratings 0 Comments 137 Invitations 0 Offline
S
Points 127 [Total 179] Ratings 0 Comments 127 Invitations 0 Offline
S
Points 111 [Total 186] Ratings 1 Comments 101 Invitations 0 Offline
S
P
1
Points 107 [Total 852] Ratings 3 Comments 57 Invitations 2 Offline
S
L
Points 86 [Total 4206] Ratings 0 Comments 86 Invitations 0 Offline
S
Points 40 [Total 50] Ratings 1 Comments 30 Invitations 0 Offline
S
Points 32 [Total 139] Ratings 0 Comments 32 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.